Preparing Leaders for the Digital Era: Addressing Challenges in a Dynamic Economy - Verma, Om Prakash Ram (Journal of Nepal Commerce Association, 2025)
The digital era has transformed the nature of leadership, requiring adaptive, innovative, and technologically proficient leaders who can navigate a rapidly evolving economic environment. This study examines the challenges and strategies involved in preparing leaders to succeed in the digital age, with a focus on the essential skills and competencies needed for effective leadership. Drawing on secondary data from scholarly literature, industry reports, and selected case studies, the research analyzes the impact of digital transformation on leadership roles and the broader economic landscape. Key challenges identified include technological disruption, skill mismatches, resistance to change, and shifting workforce expectations. The study further explores the roles of education, continuous training, and organizational culture in developing future-ready leaders. Findings suggest that effective digital-era leadership requires an integrated mix of technical knowledge, strategic vision, adaptability, and emotional intelligence. Lifelong learning, innovation, and inclusive leadership practices emerge as critical responses to economic and technological complexity. The study highlights the importance of collaboration among educational institutions, businesses, and policymakers in strengthening leadership capacity. Its practical implications include recommendations for leadership development programs emphasizing digital literacy, agility, and resilience. Overall, the study contributes valuable insights into preparing leaders for sustainable growth in a technology-driven economy.